Neuroplasticity and tinnitus: the role of Brain-Derived Neurotrophic Factor in pathogenesis and treatment - Miranda, Vincenzo; Castiglioni, Sara; Maier, Jeanette A. (Frontiers in Neuroscience, 2025)
Subjective tinnitus is defined as the perception of sound in the absence of an external acoustic source, characterized by the phantom and persistent experience of noise or indistinct, internally generated non-verbal tones. The prevalence of chronic tinnitus is estimated to range from 5 to 42% of the global population. As a significant individual and societal issue, preclinical and clinical studies have been conducted to investigate this condition and explore potential therapeutic approaches. However, a comprehensive understanding of tinnitus and a definitive treatment remain elusive. In most cases, tinnitus arises from acquired and sustained hearing loss. However, the precise mechanisms and neuronal network models responsible for the perceptual generation and persistence of tinnitus are not yet fully understood. Animal studies have demonstrated that tinnitus is associated with synaptic plasticity dysfunction in multiple brain regions, including the auditory and limbic systems. Attention has been devoted to the contribution of inflammatory cytokines and deregulated levels of Brain-Derived Neurotrophic Factor (BDNF) to the pathogenesis of tinnitus. This narrative review aims to elucidate the functional structures and biological mechanisms underlying tinnitus and propose alternative novel therapeutic approaches.